Local government innovation towards good governance through public service malls - Nurilawati, Nurilawati; Apriliyanti, Rena; Khumayah, Siti; Imawan, Khaerudin (Indonesian Journal of Multidisciplinary Science, 2024)
Public Service Mall (MPP) is an initiative to ensure good governance in Indonesia by improving the standard of good governance public services. Cirebon Regency Government continues to make various innovations through the implementation of the public service mall managed by the Investment and One-Stop Integrated Services Office (DPMPTSP) in the form of licensing and non-licensing in one place for various public services from several agencies. The author tries to provide several recommendations as follows: (1) Strengthening human resources to ensure that fresh initiatives in carrying out government duties; (2) Strengthen cooperation partners with related bureaucracy to improve the quality of services; (3) Pay attention to the technical aspects of successful implementation; (4) Increase bureaucratic commitment to the implementation and contributing to the distribution of duties and participation in public services towards good governance.